Adesão ao tratamento em adolescentes com diabetes tipo 1: dois estudos de caso - SILVA, Ingrid Ferreira Soares da (Universidade Federal do Pará, 2019)
Diabetes mellitus type 1 (DM1) is a chronic degenerative disease of major impact on the quality of life of children and adolescents. The DM1 affects predominantly children and young adults under 30 years of age with peak incidence from 10 to 14 years of age. As a chronic disease it involves changes in daily habits, and rule following becomes a key behavior to achieve such changes. This study aimed to examine factors that influenced the behavior of following the rules prescribed for the treatment of adolescents diagnosed with DM1. These rules relate specifically to the measurement of the blood glucose, the usage of the diet plan in choosing the menu and the application of insulin. The study included two adolescents aged 14 and 17 years, diagnosed with DM1, which had difficulties in controlling the disease according to medical evaluation. Also included as participants of this study were those responsible for each adolescent. The following survey instruments were used: 1) Set of interviews with the parents; 2) Inventory of parenting styles; 3) Questionnaire to evaluate the quality of life of adolescents with DM1; 4) Set of interviews with the adolescents; 5) Diabetes social support questionnaire – family version; and 6) Self monitoring forms for Treatment Compliance Behavior. The data collection was performed in the households of the adolescents. The procedure involved the following steps: 1) Selection of participants; 2) Individual interviews with the parents/guardians; 3) Individual interviews with the adolescents, including applications for inventory on their support network, characterization of the baseline behavior of measuring blood glucose, tracking diet plan, and insulin administration, interviews with positive feedback, and final interview. The results from the analysis of compliance behaviors and from the environmental factors reported by each participant throughout the research identified that the participant which emitted compliance behaviors appropriately had a good quality of life, a good level of knowledge about DM1, his parents owned a positive parenting style, perceived support provided by family, besides having a social condition satisfactory to meet the needs of the family. But the participant with a low compliance, although demonstrating a good quality of life, his parents were using a lot of negative practices, despite their parenting style being also positive, the family support perceived by the participant was inconsistent and his social status was insufficient to provide all the tools necessary for his treatment compliance. Thus, it was possible to analyze the factors that influence compliance to treatment, however further research should be conducted using a larger number of participants and also have a longitudinal character, with long-term monitoring to verify the effect of the variables described in the research along the lives of the participants.